PENGARUH LAMA PENGERINGAN BUAH LINDUR (Bruguiera ghymnorrhiza L.) TERHADAP MUT TEPUNG - Rahmadhan, Dani; Yurnalis; Leffy Hermalena (Jurnal Research Ilmu Pertanian, 2021)
One of the stages in the process of processing Lindur flour is drying, where drying is one of the determinants of flour quality. This study aims to determine the effect of drying duration of dried fruit on flour quality. The design used in this study was a completely randomized design (CRD) one factor with 5 levels of treatment and 3 replications. Observations were made on yield, water content, ash content, starch content, crude fiber content, pH value, white degree, HCN content and organoleptic test. This study results that the drying time of the fruit has an effect on yield, water content, ash content, starch content, crude fiber, white degree and HCN, but does not affect the pH value. Based on organoleptic test results, the best is flour with a drying time of 10 hours using an oven temperature of 80oC with the lowest HCN content of 0.027 ppm.